An audit on anaemia in pregnancy treatment in a local health clinic - Shalihin, Mohd Shaiful Ehsan; Mohd Hisham, Muhammad Akmal; Rozilah @ Abdul Hadi, Nur Athirah; Mohd Hisham, Nur Irdina Nabilah (Universiti Malaysia Sabah, 2023)
Anaemia in pregnancy is one of the most common conditions encountered in antenatal follow-up at primary care. Some targets need to be achieved and managed by healthcare professionals, especially at the earliest possible time and optimal level of haemoglobin in the pregnancy period. Nevertheless, some patients may end up with severe anaemia that was not successfully treated even at term. Therefore, an audit was conducted among antenatal women in a local health clinic to assess the patient’s haemoglobin level at booking and term, the management plan and to formulate strategies for improvement. This audit was conducted for two weeks using a universal sampling method in November 2022. All antenatal women who were already at term gestational period and attended the clinic during this period were included. The patients’ sociodemographic and health characteristics, haemoglobin level at booking and term as well as management plan were recorded. The data were entered into the statistical software SPSS version 23 for analysis. A total of 115 antenatal women were recruited and 87% of them were able to achieve target haemoglobin at term. Twenty-three of them had concomitant iron deficiency anaemia since the pre-pregnant state. Associated factors for successful anaemia treatment were those without concomitant IDA, those without side effects on iron supplements and those who did not require changes in the treatment course (P < 0.05). The majority of patients can achieve normal values of haemoglobin at term. Pre-pregnancy clinics to treat concomitant anaemia before pregnancy selective individualized iron supplementation to avoid side effects and maintaining the same medication groups would help treat more numbers of antenatal women with anaemia.